(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2011)
On January 23, 2008, the Colombian Constitutional Court handed down an emblematic judgment when it considered the Unconstitutionality Claim of Law No. 1021 of 2006, which established Colombia’s General Forestry Law - Judgment C-030 of 2008 - giving effective and efficient application to the command of Article 6 of ILO Convention 169. The public action of unconstitutionality was brought by Colombian citizens, who argued that ILO Convention 169 is part of the Colombian constitutional system and protects Indians and Afro-descendants, so that prior consultation with indigenous and Afro-descendant communities is essential for the validity of the General Forestry Law that was recently enacted, which was not observed. The plaintiffs argued, in summary, that the lack of prior and effective consultation with indigenous and Afro-descendant communities exploiting natural resources during the process of drafting the law was a violation of Article 6 of ILO Convention 169 and Articles 1, 2, 3, 7, 9, 13, 93 and 330, all of the Colombian Constitution.